Project Based Learning Mata Kuliah Praktek Instrument Piano II - Amalia Azzahra Kamal; Olan Yogha Pratama (Universitas Negeri Padang, 2024)
This study aims to determine and describe how project-based learning of Piano Instrument Practice II course in Music Education Study Program, Department of Sendratasik, Padang State University. This research uses qualitative methods and is descriptive, in this case it will describe how project-based learning in the Piano Instrument Practice II course. The research instrument is the researcher himself as the main instrument. Data collection is done through the stages of literature study, observation, interviews, documentation and audio and video recording. The type of data uses primary data and secondary data. The project-based learning model is the Main Performance Indicator (KPI) used by Padang State University with an assessment evaluation system in lectures. The lecture process is carried out by following the syntax in project-based learning which consists of 6 phases then the lecturer combines it with the cognitive domain of Bloom's taxonomy. The result of this research is that students make a final project, namely a new repertoire, students create a new repertoire from the mandatory material determined by the lecturer, namely minuet 1 by following the musical elements in minuet 1 and become a new discovery in lectures. The learning model used with the results obtained is well achieved.